2016
DOI: 10.1021/acs.energyfuels.6b01405
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hydrogen Chemisorption and Ethylene Hydrogenation as Predictors for Aqueous Phase Reforming of Lactose over Ni@Pt and Co@Pt Bimetallic Overlayer Catalysts

Abstract: Overlayer Pt on Ni (Ni@Pt) or Co (Co@Pt) were synthesized and tested for H2 generation from APR of lactose. H2 chemisorption descriptor showed that Ni@Pt and Co@Pt overlayer catalysts had reduced H2 adsorption strength compared to a Pt only catalyst, which agree with computational predictions. The overlayer catalysts also demonstrated lower activity for ethylene hydrogenation than the Pt only catalyst, which likely resulted from decreased H2 binding strength decreasing the surface coverage of H2. XAS results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In this work, two bimetallic overlayer catalysts, Co@Pd and Cu@Pd (core@shell), supported on silica were prepared using the directed deposition technique. Previous studies have demonstrated that supported bimetallic overlayer catalysts synthesized by this technique exhibited the designed overlayer structure and reduced adsorption strength, leading to improved reactivity in hydrogenation or hydrodeoxygenation reactions as anticipated . Catalysts were tested in vapor phase furfural hydrogenation in a fixed‐bed reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, two bimetallic overlayer catalysts, Co@Pd and Cu@Pd (core@shell), supported on silica were prepared using the directed deposition technique. Previous studies have demonstrated that supported bimetallic overlayer catalysts synthesized by this technique exhibited the designed overlayer structure and reduced adsorption strength, leading to improved reactivity in hydrogenation or hydrodeoxygenation reactions as anticipated . Catalysts were tested in vapor phase furfural hydrogenation in a fixed‐bed reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Comparably low selectivity to hydrogen was obtained during the glucose APR over carbon-supported transition metals (Pt, Pt-Ni, Pt-Ru, Pt-Sn, Pt-Ni-Sn) [17]. Lactose APR was investigated over Ni-La/Al2O3, Ni-Co/Al2O3-MgO, and Ni-La/Al2O3 catalysts [18,19] and an overlayer of Pt on Ni or Co on Pt [20].…”
Section: Introductionmentioning
confidence: 99%